Inhibition of Acetyl Coenzyme A Carboxylase Activity Restores Expression of the INO1 Gene in a snf1 Mutant Strain of Saccharomyces cerevisiae - Shirra, Margaret K. (American Society for Microbiology, 2001)
Mutations in the Saccharomyces cerevisiae SNF1 gene affect a number of cellular processes, including the expression of genes involved in carbon source utilization and phospholipid biosynthesis. To identify targets of the Snf1 kinase that modulate expression of INO1, a gene required for an early, rate-limiting step in phospholipid biosynthesis, we performed a genetic selection for suppressors of the inositol auxotrophy of snf1Δ strains. We identified mutations in ACC1 and FAS1, two genes important for fatty acid biosynthesis in yeast; ACC1 encodes acetyl coenzyme A carboxylase (Acc1), and FAS1 encodes the β subunit of fatty acid synthase. Acc1 was shown previously to be phosphorylated and inactivated by Snf1. Here we show that snf1Δ strains with increased Acc1 activity exhibit decreased INO1 transcription. Strains carrying the ACC1 suppressor mutation have reduced Acc1 activity in vitro and in vivo, as revealed by enzymatic assays and increased sensitivity to the Acc1-specific inhibitor soraphen A. Moreover, a reduction in Acc1 activity, caused by addition of soraphen A, provision of exogenous fatty acid, or conditional expression of ACC1, suppresses the inositol auxotrophy of snf1Δ strains. Together, these findings indicate that the inositol auxotrophy of snf1Δ strains arises in part from elevated Acc1 activity and that a reduction in this activity restores INO1 expression in these strains. These results reveal a Snf1-dependent connection between fatty acid production and phospholipid biosynthesis, identify Acc1 as a Snf1 target important for INO1 transcription, and suggest models in which metabolites that are generated or utilized during fatty acid biosynthesis can significantly influence gene expression in yeast.